Priority Areas For Attracting Investments In Small Business And Entrepreneurial Activity In Developed Countries - Umirov Akramjon Tursunpulotovich (Zien Journals, 2026)
Attracting investment is of great importance as a key factor in the development of small business and entrepreneurship in developed countries. In this process, state policy, financial institutions, the banking system, and private capital play a significant role. Investments not only ensure the financial stability of businesses but also create opportunities for implementing innovative projects, generating employment, and stimulating economic growth. Strategies for attracting investment for small businesses are implemented through state support, tax incentives, digital financial instruments, and business incubators. As a result, entrepreneurial activity in developed countries develops in a sustainable manner.
Keywords: investment; small business; entrepreneurship; financial institutions